Why are we vaccinating children against COVID-19?. (2021) - Kostoff, Ronald N.; Calina, Daniela; Kanduc, Darja; Briggs, Michael B.; Vlachoyiannopoulos, Panayiotis; Svistunov, Andrey A.; Tsatsakis, Aristidis
Graphical abstract: Highlights: Bulk of COVID-19 per capita deaths occur in elderly with high comorbidities. Per capita COVID-19 deaths are negligible in children. Clinical trials for these inoculations were very short-term. Clinical trials did not address long-term effects most relevant to children. High post-inoculation deaths reported in VAERS (very short-term). Abstract: This article examines issues related to COVID-19 inoculations for children. The bulk of the official COVID-19-attributed deaths per capita occur in the elderly with high comorbidities, and the COVID-19 attributed deaths per capita are negligible in children. The bulk of the normalized post-inoculation deaths also occur in the elderly with high comorbidities, while the normalized post-inoculation deaths are small, but not negligible, in children. Clinical trials for these inoculations were very short-term (a few months), had samples not representative of the total population, and for adolescents/children, had poor predictive power because of their small size. Further, the clinical trials did not address changes in biomarkers that could serve as early warning indicators of elevated predisposition to serious diseases. Most importantly, the clinical trials did not address long-term effects that, if serious, would be borne by children/adolescents for potentially decades. A novel best-case scenario cost-benefit analysis showed very conservatively that there are five times the number of deaths attributable to each inoculation vs those attributable to COVID-19 in the most vulnerable 65+ demographic. The risk of death from COVID-19 decreases drastically as age decreases, and the longer-term effects of the inoculations on lower age groups will increase their risk-benefit ratio, perhaps substantially.